Characterization and Transplantation of CD73-Positive Photoreceptors Isolated from Human iPSC-Derived Retinal Organoids - Gagliardi, Giuliana (Stem Cell Reports, 2018)
Photoreceptor degenerative diseases are a major cause of blindness for which cell replacement is one of the most encouraging strategies. For stem cell-based therapy using human induced pluripotent stem cells (hiPSCs), it is crucial to obtain a homogenous photoreceptor cell population. We confirmed that the cell surface antigen CD73 is exclusively expressed in hiPSC-derived photoreceptors by generating a fluorescent cone rod homeobox (Crx) reporter hiPSC line using CRISPR/Cas9 genome editing. We demonstrated that CD73 targeting by magnetic-activated cell sorting (MACS) is an effective strategy to separate a safe population of transplantable photoreceptors. CD73+ photoreceptor precursors can be isolated in large numbers and transplanted into rat eyes, showing capacity to survive and mature in close proximity to host inner retina of a model of photoreceptor degeneration. These data demonstrate that CD73+ photoreceptor precursors hold great promise for a future safe clinical translation.